Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
C.(-31)
Step-by-step explanation:
= 5 - 4(1 + 2^3)
= 5 - 4(1 + (2 . 2 . 2))
= 5 - 4(1 + (4 . 2))
= 5 - 4(1 + 8)
= 5 - 4(9)
= 5 - (4 . 9)
= 5 - 36
= (-31)
>> Answer
_________
[tex] \: [/tex]
5 - 4(1 + 2³) = ?
= 5 - (4(1) + 4(2³))
= 5 - (4 + 4(8))
= 5 - (4 + 32)
= 5 - 36
= -31
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.